Evaluation Of User Satisfaction Of The Hospital Management Information System At Pku Muhammadiyah Yogyakarta Hospital: Eucs Method - Yuspita Sari, Rizky (Infomasi dan Promosi Kesehatan, 2023)
Background: PKU Muhammadiyah Yogyakarta Hospital has implemented SIMRS since 1997 which was originally based on the DOS operating system. SIMRS in PKU has never been evaluated for system user satisfaction. The purpose of this research is to see SIMRS user satisfaction when viewed from the elements that exist in end user computing satisfaction. System evaluation is important to do to find out how far the system is implemented and to find out aspects - Aspects that need to be addressed. One of the evaluation methods that can be used is the EUCS method, the EUCS method is used to measure the level of satisfaction of system users by comparing expectations and reality. Methods : The research design is descriptive with a quantitative approach. The data in this study were collected through questionnaires. The population in this study were all SIMRS users at PKU Muhammadiyah Yogyakarta Hospital. The sample selected in this study amounted to 65 people. Sampling was done by simple random sampling technique. Result : The characteristics of respondents in terms of gender, namely women have a percentage of 83.1% and men 16.9%. The highest percentage share of age is owned by the age group of 41-50 years with a percentage of 46.2%. The highest percentage work unit is owned by the inpatient polyclinic unit with a percentage of 55.3%. The last education with the highest percentage is owned by D-3. And finally, the highest respondent's length of service is 21-30 years with a percentage of 46.2%. The content variable gets an average value of 76,9%, the accuracy variable gets an average value of 78,4%, the format variable gets an average value of 76,76%, the timeliness variable gets an average value of 76,25% and the ease of use variable gets the average value is 79,2%. Conclusion : The results in this study of SIMRS users at PKU Muhammadiya Yogyakarta Hospital were satisfied with the SIMRS application